“Desarrollo de un sistema de control de inventario para la toma de decisiones en la empresa La Clínica del Computador”. - Escobar López, William Alexander (2023)
Technology based on computer systems has had a high impact on the commercial sector of SMEs which allowed them to change from physical to digital in their marketing processes through the development and implementation of applications or systems that automate processes and give high benefits in the visualization of results of the company's productivity. The objective was to develop an inventory control system for decision-making in La Clínica del Computador La Maná". The methodology used was: descriptive, field, and bibliographic level, and the data collection technique was a survey made up of 5 questions, plus an interview made up of 8 equal questions that will present later. The population for this study was 625 clients of the company, of which 238 were taken. The main results indicate that 57% of those surveyed mentioned that if the inventory system helps the organization, why on the other hand, 43% mention that the inventory control system must have security when selling a product, while 31% indicate that it increases the productivity of the company. The results obtained in the investigation allowed the development of the system and the evaluation of its correct functioning, at present these systems store data concurrently, which have become essential tools for companies since they make available to process information, and improve procedures, thus providing better performance, security, and agility avoiding the loss of information. As well as the Power Bi tool, which allows data analysis for decision-making.